Pre-Exposure Prophylaxis Barriers, Facilitators and Unmet Need Among Rural People Who Inject Drugs: A Qualitative Examination of Syringe Service Program Client Perspectives - Surratt, Hilary L.; Yeager, Hannah J.; Adu, Akosua; González, Evelyn A.; Nelson, Elizabeth O.; Walker, Tamara (Frontiers in Psychiatry, 2022)
Background: People who inject drugs (PWID) are at high risk for HIV infection, yet in rural areas PWID are understudied. Kentucky is notable for heavy rural HIV burden, yet despite high need and the strong evidence for Pre-Exposure Prophylaxis (PrEP) as a gold-standard biomedical HIV prevention tool, scale up has been limited among PWID in Kentucky and elsewhere. Methods: Data are drawn from an ongoing NIH-funded study designed to adapt and integrate a PrEP initiation intervention for high-risk PWID in two rural syringe service programs (SSPs) in southeastern Kentucky. As part of this initiative, a qualitative study guided by PRISM (Practical, Robust, Implementation, and Sustainability Model) was undertaken to gather SSP client perspectives on intervention needs related to PrEP as well as tangible supports for and barriers to PrEP uptake. Recruitment and interviews were conducted during September-November 2021 with 26 clients, 13 from each of the two SSP sites. Interviews were recorded, transcribed verbatim and verified. A detailed coding scheme was developed and applied by independent coders using NVivo. All study procedures were approved by the University IRB. Results: Participants were 96% white, 42% female, with a median age of 41 years (range 21-62); all reported injection use within the past month. Overall, we found low PrEP awareness among this sample, yet interest in PrEP was high. Clients reported overwhelmingly positive experiences at the SSPs, considering them trusted and safe locations to receive health services, and were enthusiastic about the integration of co-located PrEP services. Lack of basic HIV and PrEP knowledge were in evidence, which contributed to common misperceptions about personal risk for HIV. Stigma related to substance use and HIV arose as a concern for PrEP uptake. Noted tangible barriers included inconsistent access to phone service and transportation. Primary supports included high levels of insurance coverage, consistent pharmacy access, and histories with successful medication management for other health conditions. Conclusions: Drawing on the critical perspectives of people with llived experience our findings provide important and actionable information on individual and environmental barriers and facilitators of PrEP uptake among rural PWID at risk for HIV infection.